(untitled) (Revista Archai, 2025)
This paper aims to establish a homology between two forms of art: the portraits of Octavian Augustus and Augustan poetry, particularly the works of Horace, Ovid, Propertius, and Virgil. The theoretical frameworks of Nora (1989), Assmann (1995 and 2011), Halbwachs (1968), and Galinsky (2014-2016) are mobilized to support the argument that both artistic expressions can be interpreted as vehicles of collective memory and cultural memory, serving the perpetuation of power and art